Building mobile apps for underrepresented mental health care consumers: A grounded theory approach. Issue 6 (1st November 2016) - Leung, Ricky; Hastings, Julia F.; Keefe, Robert H.; Brownstein-Evans, Carol; Chan, Keith T.; Mullick, Rosemary
ABSTRACT: Cell phone mobile application ("app") use has risen dramatically within the past several years. Many individuals access apps to address mental health issues. Unlike individuals from privileged backgrounds, individuals from oppressed backgrounds may rely on apps rather than costly mental health treatment. To date, very little research has been published evaluating mental health apps' effectiveness. This article focuses on three methods through which grounded theory can facilitate app development and evaluation for people underrepresented in mental health care. Recommendations are made to advance mobile app technology that will help clinicians provide effective treatment, and consumers to realize positive treatment outcomes.